Peran Otoritas Jasa Keuangan (OJK) dalam Pengembalian Dana Investor atas Delisting Saham Emiten Di BEI Akibat Praktik Manipulasi Pasar di Pasar Modal Ditinjau dari UU OJK Dihubungkan dengan UU Pasar Modal - Aidil Rakha Nurul Hadi Dimalouw; Frency Siska (Bandung Conference Series: Law Studies, 2022)
OJK (Financial Services Authority) is an institution that is independent and free from interference from other parties, which has the functions, duties and authority to regulate, supervise, examine and investigate all activities in the financial sector. Several aspects included in the scope of supervision of the Financial Services Authority are financial service activities in the banking sector, capital market, financial service activities in the insurance sector, pension funds, financing institutions, and other financial service institutions. One of the sectors supervised by OJK is the capital market. Market manipulation in the capital market can be interpreted as an attempt to interfere with the free and fair operation of the market and create a false picture. The Capital Market Law prohibits the practice of market manipulation by stipulating that each party is prohibited from taking actions, either directly or indirectly, to create a false or misleading picture regarding trading activities, market conditions, or securities prices on the stock exchange. PT. Sekawan Intipratama with the stock code SIAP from 2014 to 2015, the price movement chart is very volatile. In the end, the IDX delisted the SIAP issuer, because it was suspected that the share price was manipulated to make it appear as if the stock was active and liquid. As a result, investors' funds were held back because SIAP's shares were illiquid. The return of investor funds due to the delisting of issuers due to market manipulation practices in the capital market cannot be carried out because existing regulations do not yet regulate this. In POJK Number 49/POJK.04/2016 concerning the Investor Protection Fund that the payment of compensation to investors, as a result of manipulation not written in the criteria for reimbursement of funds by the Investor Protection Fund. OJK as the institution that oversees activities in the capital market, is advised to make clearer regulations, at least in the form of a Financial Services Authority Regulation (POJK) regarding the return of investor funds due to market manipulation practices in the capital market so that investors feel safe to invest in the Capital Market. OJK (Otoritas Jasa Keuangan) adalah lembaga yang independen dan bebas dari campur tangan pihak lain, yang mempunyai fungsi, tugas, dan wewenang pengaturan, pengawasan, pemeriksaan, dan penyidikan terhadap seluruh kegiatan disektor keuangan. Beberapa aspek yang termasuk dalam lingkup pengawasan Otoritas Jasa Keuangan adalah kegiatan jasa keuangan di sektor Perbankan, pasar modal, kegiatan jasa keuangan di sektor perasuransian, dana pensiun, lembaga pembiayaan, dan lembaga jasa keuangan lainnya. Salah satu sektor yang diawasi oleh OJK ini diantaranya adalah pasar modal. Manipulasi pasar pada pasar modal dapat diartikan sebagai usaha yang dilakukan untuk mencampuri operasi pasar yang bebas dan wajar dan membuat gambaran yang semu. UU Pasar Modal melarang praktik manipulasi pasar tersebut dengan mengatur bahwa setiap pihak dilarang melakukan tindakan, baik langsung maupun tidak langsung, dengan dengan tujuan untuk menciptakan gambaran semu atau menyesatkan mengenai kegiatan perdagangan, keadaan pasar, atau harga efek di bursa efek. PT. Sekawan Intipratama dengan kode saham SIAP pada 2014 hingga 2015 , grafik pergerakan harganya sangat fluktuaktif. BEI pada akhirnya melakukan delisting pada emiten SIAP, karena adanya dugaan harga saham tersebut dimanipulasi agar seolah saham itu aktif dan likuid. Akibatnya, dana investor tertahan karena saham SIAP tidak likuid. Pengembalian dana investor akibat delisting terhadap emiten karena praktik manipulasi pasar di pasar modal tidak dapat dilaksanakan karena regulasi yang ada belum mengatur hal tersebut. Dalam POJK Nomor 49/POJK.04/2016 tentang Dana Perlindungan Pemodal bahwa Pembayaran ganti rugi kepada Pemodal, akibat dari manipulasi tidak tertulis dalam kriteria penggantian dana oleh Dana Perlindungan Pemodal. OJK selaku lembaga yang mengawasi kegiatan di pasar modal, disarankan agar membuat peraturan yang lebih jelas setidaknya berupa Peraturan Otoritas Jasa Keuangan (POJK) tentang pengembalian dana investor akibat praktik manipulasi pasar pada pasar modal sehingga para investor merasa aman untuk berinvestasi di Pasar Modal.